Narrator and Epic Tradition: Uligers of Bura Barnakov - E. N. Kuzmina (Научный диалог)
The article is devoted to the study of the heroic tales of the Buryat-Uligers, performed by B. Barnakov. Particular attention is paid to the repertory of this storyteller. The question of the preservation of the plot structure of works and storytelling memory in the conditions of the extinction of the epic tradition, when the epic environment and regular performance have already disappeared, is considered. The results of a comparative analysis of the plots of legends and their poetics are presented in the article. The relevance and novelty of the study is due to the fact that B. Barnakov’s legends have not yet entered the research field and have not become the subject of special study. In addition, the inclusion of one of the texts for publication in the series “Monuments of Folklore of the Peoples of Siberia and the Far East” makes a comprehensive study of the creative heritage of the uligersha relevant. The author pays special attention to stereotypes in these legends, highlighting intertextual and situational “common places”. The conclusion is made that the preservation of the narrative memory and the fullness of the repertory of the uligersha in the absence of a natural epic environment indicates the inertial stability of the epic tradition, due to the sacred nature of the heroic epos.